(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Pleural effusion can occur with varied clinical presentations. Objective: The purpose of the present study was to see the demographic characteristics and clinical profiles of patients presented with exudative pleural effusion. Methodology: This cross-sectional study was carried out at medicine indoor department of Sylhet MAG Osmani Medical College Hospital, Sylhet over a period of six month from October 2009 to March 2010. Patients who were admitted with pleural effusion were selected as the study population. Pleural fluid was collected by a physician. The laboratory tests were performed in the Department of Laboratory medicine of the Hospital. The details history of age, sex, socio-economic condition, clinical features were collected from the patients. Results: A total of 50 cases were selected consecutively in the study. The mean age of the patients was 44.5±12.86 years. Male to female ratio was 2.1:1. Over half of the patients (54.0%) was poor; 32.0% cases was middle class and 14.0% cases was rich. Low-rade fever (92.0%), cough (86.0%), weight loss (74.0%) and dyspnoea (56.0%) were found as the most common symptoms of exudative pleural effusion. Conclusion: In conclusion middle age adult male living in poor socio-sconomic condition are most commonly suffering from exudative pleural effusion. Journal of National Institute of Neurosciences Bangladesh, July 2022;8(2):167-170